Modeling of a CPV/T-ORC Combined System Adopted for an Industrial User - Carlo Renno; Fabio Petito; Diana D’Agostino; Francesco Minichiello (Energies, 2020)
The increasing energy demand encourages the use of photovoltaic solar systems coupled to organic rankine cycle (ORC) systems. This paper presents a model of an ORC system coupled with a concentrating photovoltaic and thermal (CPV/T) system. The CPV/T-ORC combined system, described and modeled in this paper, is sized to match the electrical load of a medium industrial user located in the South of Italy. A line-focus configuration of the CPV/T system, constituted by 16 modules with 500 triple-junction cells, is adopted. Different simulations have been realized evaluating also the direct normal irradiance (DNI) by means of the artificial neural network (ANN) and considering three input condition scenarios: Summer, winter, and middle season. Hence, the energy performances of the CPV/T-ORC system have been determined to evaluate if this integrated system can satisfy the industrial user energy loads. In particular, the peak power considered for the industrial machines is about 42 kW while other electrical, heating or cooling loads require a total peak power of 15 kW; a total electric average production of 7500 kWh/month is required. The annual analysis shows that the CPV/T-ORC system allows satisfying 100% of the electric loads from April to September; moreover, in these months the overproduction can be sold to the network or stored for a future use. The covering rates of the electrical loads are equal to 73%, 77%, and 83%, respectively for January, February, and March and 86%, 93%, and 100%, respectively for October, November, and December. Finally, the CPV/T-ORC combined system represents an ideal solution for an industrial user from the energy point of view.